WOMAN IN THE GREY AREA' DALAM FILSAFAT DISCOURSE: MANUSIA, PEREMPUAN DAN SEKS WORKER - Suharnanik, Suharnanik (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2015)
Humans as a single unified whole that unites between soul and body. Homan reputed to exist if that organism is reputed exist, it means meaning full that determine human acknowledged. The sex of human organism is male or female even gray areas are determined based on objectivity and subjectivity that inherent in visible or not visible. In the word of "woman" as a social reality that must be accepted as a voluntary or forced act. Whore is a deep human organism in the social reality that containing of human behavior subjectively or objectively, behavioral formed consciously or unconsciously intentionally or unintentionally. Behavior is forming a consciousness as a marker or meaning full of human. Society and culture is responsible for the formation of meaning of prostitutes, whether the organism is included in the categorization of black, white or grayKeywords: Human, Woman, and Seks WorkerÂ